Identification of Quercetin and Gallic Acid in Phyllanthus niruri extract by Thin Layer Chromatography - Mukesh Singh Chhawari, Ram Kumar Sahu, Naveen K Choudhary (International Journal of Advanced Science and Technology, 2021)
Phyllanthus niruri is used by traditional healers to cure many diseases. Quercetin and gallic acid belong to flavonoids, which have various pharmacological activities and are used in curing various diseases. To date, there is no information on the determination of quercetin and gallic acid in Phyllanthus niruri by employing thin layer chromatography (TLC). Therefore, it is of utmost importance to develop a fingerprint profile of quercetin and gallic acid in Phyllanthus niruri using TLC technique. It was planned to develop a TLC method for the estimation of quercetin and gallic acid in Phyllanthus niruri. The maceration method was used for the preparation of petroleum ether and hydroalcoholic extracts from the aerial part of Phyllanthus niruri. The phytochemical studies were performed for both extracts, while the TLC study was performed for the hydroalcoholic extract. The hydroalcoholic extract contained a higher number of chemical constituents than the petroleum ether extract. The findings of the TLC study of the hydroalcoholic extract showed Rf 0.54 and 0.26 in the mobile phase toluene: Ethyl acetate: formic acid (5:4:1) and toluene: Ethyl acetate: formic acid (7:5:1) and the same Rf value was found for pure quercetin and gallic acid. Thus, the TLC study confirmed the occurrence of quercetin and gallic acid in the hydroalcoholic extract of Phyllanthus niruri. This developed TLC method provides a simple, inexpensive and easy technique for the assessment of the quercetin and gallic acid in Phyllanthus niruri.